Intervención del terapista respiratorio en paciente masculino de 75 años con EPOC. - Vera Marmolejo, Sandra Lisbeth (2022)
Chronic obstructive pulmonary disease is a pathology that is among the 5 leading causes of death worldwide, the same one that causes slow, progressive and irreversible damage to the distal structures of the respiratory tract. A clinical case of a 75-year-old male patient diagnosed with COPD is presented. The objective of this project was to describe the usefulness of oxygen support in this type of patient. It was obtained as a result that both low-flow and high-flow oxygenation devices play a fundamental role in maintaining adequate levels of oxygenation in episodes of desaturation present in the exacerbation phases of the pathology.